2015 Southern Taurid fireballs and asteroids 2005 UR and 2005 TF50. Issue 1 (29th May 2016) - Olech, A.; Żołądek, P.; Wiśniewski, M.; Rudawska, R.; Bęben, M.; Krzyżanowski, T.; Myszkiewicz, M.; Stolarz, M.; Gawroński, M.; Gozdalski, M.; Suchodolski, T.; Węgrzyk, W.; et al.
Abstract: On the night of October 31, 2015 two bright Southern Taurid fireballs occurred over Poland, being one of the most spectacular bolides of this shower in recent years. The first fireball – PF311015a Okonek – was detected by six video stations of Polish Fireball Network (PFN) and photographed by several bystanders, allowing for precise determination of the trajectory and orbit of the event. The PF311015a Okonek entered Earth's atmosphere with the velocity of 33.2 ± 0.1 km s −1 and started to shine at height of 117.88 ± 0.05 km. The maximum brightness of −16.0 ± 0.4 mag was reached at height of 82.5 ± 0.1 km. The trajectory of the fireball ended at height of 60.2 ± 0.2 km with terminal velocity of 30.2 ± 1.0 km s −1 . The second fireball – PF311015b Ostrowite – was detected by six video stations of PFN. It started with velocity of 33.2 ± 0.1 km s −1 at height of 108.05 ± 0.02 km. The peak brightness of −14.8 ± 0.5 mag was recorded at height of 82.2 ± 0.1 km. The terminal velocity was 31.8 ± 0.5 km s −1 and was observed at height of 57.86 ± 0.03 km. The orbits of both fireballs are similar not only to orbits of Southern Taurids and comet 2P/Encke, but even closer resemblance was noticed for orbits of 2005 UR and 2005 TF50 asteroids. Especially the former object is interesting because of its close flyby during spectacular Taurid maximum in 2005. We carried out a further search to investigate the possible genetic relationship of Okonek and Ostrowite fireballs with both asteroids, that are considered to be associated with Taurid complex. Although, we could not have confirmed unequivocally the relation between fireballs and these objects, we showed that both asteroids could be associated, having the same origin in a disruption process that separates them.